2020
DOI: 10.3390/pharmaceutics12050422
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular-Ca2+-Induced Decrease in Small Molecule Electrotransfer Efficiency: Comparison between Microsecond and Nanosecond Electric Pulses

Abstract: Electroporation—a transient electric-field-induced increase in cell membrane permeability—can be used to facilitate the delivery of anticancer drugs for antitumour electrochemotherapy. In recent years, Ca2+ electroporation has emerged as an alternative modality to electrochemotherapy. The antitumor effect of calcium electroporation is achieved as a result of the introduction of supraphysiological calcium doses. However, calcium is also known to play a key role in membrane resealing, potentially altering the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…MD simulations have already proved that the presence of Ca 2+ has almost no effect on the pore lifetime [ 65 ]. Calcium changes though the conductivity of the electroporation buffer and consequently might have an impact on transmembrane voltage generation [ 66 ]. This effect is more pronounced once nanosecond PEFs are applied.…”
Section: Discussionmentioning
confidence: 99%
“…MD simulations have already proved that the presence of Ca 2+ has almost no effect on the pore lifetime [ 65 ]. Calcium changes though the conductivity of the electroporation buffer and consequently might have an impact on transmembrane voltage generation [ 66 ]. This effect is more pronounced once nanosecond PEFs are applied.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Faraday law of electromagnetic induction, a TMF with a higher frequency can generate an intenser electric field, leading to the occurrence of EP effect. Similar to the EP studies with pulsed electric fields, in the condition of the equal energy import, the EP can be intensified with a pulse with a higher frequency, supported by the experimental studies [43] (indicated by the shift of fluorescence dyes) and the simulation studies [44] (indicated by the pore density and…”
Section: Sub-microsecond and Nanosecond Pulse Simulation Resultsmentioning
confidence: 64%
“…According to the Faraday law of electromagnetic induction, a TMF with a higher frequency can generate an intenser electric field, leading to the occurrence of EP effect. Similar to the EP studies with pulsed electric fields, in the condition of the equal energy import, the EP can be intensified with a pulse with a higher frequency, supported by the experimental studies [43] (indicated by the shift of fluorescence dyes) and the simulation studies [44] (indicated by the pore density and radius).…”
Section: Resultsmentioning
confidence: 70%